PENGARUH JUMLAH DEWAN KOMISARIS, STRUKTUR MODAL PERUSAHAAN, DAN JUMLAH RAPAT KOMITE AUDIT TERHADAP PROFITABILITAS PERUSAHAAN PADA SEKTOR TEKNOLOGI YANG TERDAFTAR DI BEI TAHUN 2020- 2021 - Jovanic, Jason (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2024)
This research aims to analyze the influence of the number of board of commissioners, capital structure of the company, and the number of audit committee meetings on the profitability of technology companies listed on the Indonesia Stock Exchange from 2020 to 2021. The research adopts a quantitative approach using secondary data obtained from the annual reports of technology companies from idx.co.id and the official websites of the companies. Data analysis is conducted using multiple linear regression. The results of the research indicate that, partially, the number of board of commissioners has a positive impact on the profitability of technology companies. However, the capital structure of the company and the number of audit committee meetings cannot be proven to have an influence on profitability. Furthermore, the results of the research reveal that, collectively, the number of board of commissioners, capital structure of the company, and the number of audit committee meetings have an impact on the profitability of technology companies during the period of 2020-2021.